2004
DOI: 10.1074/jbc.m400802200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of the Reactive Site in the First Kunitz-type Domain of Human Tissue Factor Pathway Inhibitor-2

Abstract: Human tissue factor pathway inhibitor-2 (TFPI-2) is a Kunitz-type proteinase inhibitor that regulates a variety of serine proteinases involved in coagulation and fibrinolysis through their non-productive interaction with a P 1 residue (Arg-24) in its first Kunitz-type domain (KD1). Previous kinetic studies revealed that TFPI-2 was a more effective inhibitor of plasmin than several other serine proteinases, but the molecular basis for this specificity was unclear. In this study, we employed molecular modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
67
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 59 publications
10
67
0
1
Order By: Relevance
“…Comparison of the Inhibitory Properties of KD1-WT, KD1-L17R, and BPTI-In agreement with previous studies (22,23), KD1-WT inhibited pKLK, FXIa, and Pm with K i ‫ء‬ values of 25, 18, and 6 nM, respectively ( Fig. 3 and Table 1).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Comparison of the Inhibitory Properties of KD1-WT, KD1-L17R, and BPTI-In agreement with previous studies (22,23), KD1-WT inhibited pKLK, FXIa, and Pm with K i ‫ء‬ values of 25, 18, and 6 nM, respectively ( Fig. 3 and Table 1).…”
Section: Resultssupporting
confidence: 72%
“…2 and 3 are consistent with the concept that coagulation proteases prefer a nonpolar residue at P2Ј position in their substrates/inhibitors (6,17,23,42). In this context, KD1-L17R has no inhibitory activity toward pKLK, FXIa, and FVIIa/sTF.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As a result of numerous adverse renal complications associated with its use in surgery, aprotinin was voluntarily withdrawn from the market by the manufacturer in 2007 and replaced with antifibrinolytic agents such as e-aminocaproic acid and tranexamic acid in these patients. The mechanism whereby aprotinin induces renal dysfunction in these patients is not known with certainty, but presumably involves uptake of aprotinin by proximal tubule cells (Vio et al, 1998), where it has been shown to inhibit tubule kallikrein secretion, prostaglandin and renin synthesis, and bradykinin release (Seto et al, 1983).Our laboratory has previously reported that an R24K mutant of the first Kunitz-type domain of human tissue factor pathway inhibitor-2, designated R24K KD1, exhibits plasmin inhibitory activity comparable with aprotinin (Chand et al, 2004), suggesting its potential as an alternative to aprotinin in cardiac surgery. Whether R24K KD1 exhibits the same nephrotoxic effects as aprotinin in an animal model has not been investigated.…”
mentioning
confidence: 99%